2022
DOI: 10.1111/1556-4029.14969
|View full text |Cite
|
Sign up to set email alerts
|

Separation of overlapping fingerprints by principal component analysis and multivariate curve resolution–alternating least squares analysis of hyperspectral imaging data

Abstract: Overlapping fingerprints are often found at crime scenes, but only individual fingerprints separated from each other are admissible as evidence in court. Fingerprint components differ slightly among individuals, and thus their fluorescence spectra also differ from each other. Therefore, the separation of overlapping fingerprints using the difference of the fluorescence spectrum was performed with a hyperspectral imager. Hyperspectral data (HSD) of overlapping fingerprints were recorded under UV LED excitation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…For example, using fluorescence spectroscopy and HIS, Akiba et al developed a method of separating overlapped fingerprints. 263 In cases where two sets of FMs exist on top of one another, it is usually impossible to distinguish between them. However, measuring the fluorescence spectra of the FMs provided insight into the differences among these similar spectra.…”
Section: ■ Physics/pattern Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, using fluorescence spectroscopy and HIS, Akiba et al developed a method of separating overlapped fingerprints. 263 In cases where two sets of FMs exist on top of one another, it is usually impossible to distinguish between them. However, measuring the fluorescence spectra of the FMs provided insight into the differences among these similar spectra.…”
Section: ■ Physics/pattern Interpretationmentioning
confidence: 99%
“…Spectroscopic techniques are also being utilized to solve unique challenges in FM analysis. For example, using fluorescence spectroscopy and HIS, Akiba et al developed a method of separating overlapped fingerprints . In cases where two sets of FMs exist on top of one another, it is usually impossible to distinguish between them.…”
Section: Physics/pattern Interpretationmentioning
confidence: 99%
“…Optical methods – Preliminary/Pilot studies – A couple of optical methods were proposed to detect latent fingermarks: UV-induced luminescence HSI combined with chemometric tools to separate overlapped fingermarks left on TLC plates [ 206 ]; reflected UV polarization imaging to detect fingermarks on flat, non-porous substrates [ 207 ]; short-wave 266 nm UV laser to induce long-wave UV luminescence of fingermarks on porous substrates [ 208 , 209 ] – note: the authors observed some laser-induced degradation of the fingermarks and the substrates; reflected MWIR imaging to detect fingermarks on the adhesive-side of tapes, and on flat, non-porous substrates [ 210 ]; OCT to separate “overlapped” or hidden fingermarks [ 211 ] – note: the so-called “overlapped” fingermarks were actually left on four stacked glass slides.…”
Section: Fingermark Visualisationmentioning
confidence: 99%
“…The principal components of the standardized matrix are calculated to obtain the principal component matrix, as shown in Formula (15) [26].…”
Section: Power Load Cluster Analysis With Improved Lofmentioning
confidence: 99%